The CC‐NB‐LRR OsRLR1 mediates rice disease resistance through interaction with OsWRKY19. Issue 5 (17th January 2021) - Du, Dan; Zhang, Changwei; Xing, Yadi; Lu, Xin; Cai, Linjun; Yun, Han; Zhang, Qiuli; Zhang, Yingying; Chen, Xinlong; Liu, Mingming; Sang, Xianchun; Ling, Yinghua; et al.
Summary: Nucleotide‐binding site–leucine‐rich repeat (NB‐LRR) resistance proteins are critical for plant resistance to pathogens; however, their mechanism of activation and signal transduction is still not well understood. We identified a mutation in an as yet uncharacterized rice coiled‐coil (CC)‐NB‐LRR, Oryza sativa RPM1‐like resistance gene 1 ( OsRLR1 ), which leads to hypersensitive response (HR)‐like lesions on the leaf blade and broad‐range resistance to the fungal pathogen Pyricularia oryzae (syn. Magnaporthe oryzae ) and the bacterial pathogen Xanthomonas oryzae pv. oryzae, together with strong growth reduction. Consistently, OsRLR1 ‐overexpression lines showed enhanced resistance to both pathogens. Moreover, we found that OsRLR1 mediates the defence response through direct interaction in the nucleus with the transcription factor OsWRKY19. Down‐regulation of OsWRKY19 in the rlr1 mutant compromised the HR‐like phenotype and resistance response, and largely restored plant growth. OsWRKY19 binds to the promoter of OsPR10 to activate the defence response. Taken together, our data highlight the role of a new residue involved in the NB‐LRR activation mechanism, allowing identification of a new NB‐LRR downstream signalling pathway.